Study guides

☆☆

Q: What is 3t plus 2s plus t plus 5s?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

4

3t+11 = 29 3t = 29-11 3t = 18 t = 6

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

Related questions

That's a simple example of system of equations. There are quite a number of methods for solving those, but the easiest here would be to calculate one variable from first equation and substitute it into second. 2s + 3t = 28 5s + 6t = 61 Let's calculate s from the first equation: 2s + 3t = 28, 2s = 28 - 3t s = 14 - 3t/2 Substitute s into second equation 5s + 6t = 61, 5(14 - 3t/2) + 6t = 61, 70 - 15t/2 + 6t = 61, 70 - 3t/2 = 61, 3t/2 = 9, t = 6. We can then substitute t back into first equation: 2s + 3t = 28, 2s + 3 * 6 = 28, 2s = 10, s = 5. So the final answer is: s = 5 t = 6

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

s = 7, t = -3

if you mean T-3t+2t+4 (T and t is different variables):T-3t+2t+4=T-t+4if you mean t-3t+2t+4:t-3t+2t+4=4

17

5t + 1

4

3t+11 = 29 3t = 29-11 3t = 18 t = 6

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

As it is written, it makes no sense. If you mean: (s)(3t)(2s-2t) then the answer is 6s^2t - 6st^2 or (6st)(s-t) If the statement is something else, then the answer is something else

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

People also asked